2019
DOI: 10.1021/acs.iecr.9b04974
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and Prediction of Thermal Conductivity Using the Redlich–Kwong Cubic Equation of State and the Geometric Similitude Concept for Pure Substances and Mixtures

Abstract: In this work, a model for the thermal conductivity of nonpolar and polar substances is developed based on the geometric similitude concept between the P−v (molar volume)−-T and T−k (thermal conductivity)−-P plots. The Redlich−Kwong equation of state is used to perform the geometric similitude. The parameters of the model are estimated by fitting experimental data of saturated liquid and saturated vapor. Generalized expressions in terms of the normal boiling point are proposed for the parameters of n-alkanes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 71 publications
0
10
0
1
Order By: Relevance
“…In eq 12, AADμ is the average absolute relative deviation between the calculated values (μ cal ) and pseudoexperimental values (μ exp ), 79 N is the number of experimental data, and μ is the viscosity at Pa•s. The objective function has been used to estimate the parameters associated with transport properties such as viscosity 17−20 and thermal conductivity 82 in the literature. The optimum parameters in terms of the number of carbon atoms are presented in Figure 1 and the following facts can be noticed:…”
Section: Preliminary Analysis Of the Viscosity Model Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…In eq 12, AADμ is the average absolute relative deviation between the calculated values (μ cal ) and pseudoexperimental values (μ exp ), 79 N is the number of experimental data, and μ is the viscosity at Pa•s. The objective function has been used to estimate the parameters associated with transport properties such as viscosity 17−20 and thermal conductivity 82 in the literature. The optimum parameters in terms of the number of carbon atoms are presented in Figure 1 and the following facts can be noticed:…”
Section: Preliminary Analysis Of the Viscosity Model Parametersmentioning
confidence: 99%
“…The exception is related to the first substance of the homologous series, due to the different experimental behaviors when it is compared to the rest of the substances. 37,38,82,87,88 The literature review showed that these substances can be modeled as a separate functional group.…”
Section: Generalization Procedures Of the Viscositymentioning
confidence: 99%
“…Besides the empirical methods, correlations based on popular equations of state, such as the Peng and Robinson 31 (PR EoS), have also been developed. 32,33 To these equations the theorem of corresponding states has been applied, that is, similarity between p-v-T and T-λ-p behavior (Geometric Similitude Concept). 34 Teja and Tarlneu 35 introduced an effective carbon number concept to calculate the thermal conductivity of pure liquids and liquid mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the empirical methods, correlations based on popular equations of state, such as the Peng and Robinson (PR EoS), have also been developed. , To these equations the theorem of corresponding states has been applied, that is, similarity between p-v-T and T-λ-p behavior (Geometric Similitude Concept) …”
Section: Introductionmentioning
confidence: 99%
“…Cuando se carece de datos experimentales, esta importante propiedad debe ser estimada utilizando modelos empíricos, teóricos o semi-teóricos (Bonyadi y Rostami, 2017) y los basados en redes neuronales e inteligencia artificial (Hezave et al, 2012). Ejemplo de estos modelos son los desarrollados por Hopp y Gross (2019), Cardona et al (2019), Tomassetti et al (2020), Chen et al (2020). No obstante, estos modelos han sido utilizados para predecir sustancias orgánicas y no se han extendido a líquidos iónicos.…”
Section: Introductionunclassified